2017
DOI: 10.1007/s10468-016-9658-8
|View full text |Cite
|
Sign up to set email alerts
|

The Nodal Cubic is a Quantum Homogeneous Space

Abstract: The cusp was recently shown to admit the structure of a quantum homogeneous space, that is, its coordinate ring B can be embedded as a right coideal subalgebra into a Hopf algebra A such that A is faithfully flat as a B-module. In the present article such a Hopf algebra A is constructed for the coordinate ring B of the nodal cubic, thus further motivating the question which affine varieties are quantum homogeneous spaces.Keywords Hopf algebra · Quantum homogeneous space · Singular curve · Noncommutative Galois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Goodearl and Zhang showed [11,Construction 1.2] that every cusp y m = x n , where m and n are coprime integers with m > n ≥ 2, is a quantum homogeneous space in a noetherian Hopf domain of Gel'fand-Kirillov dimension 2. In [17], Kraehmer and the second author showed that the nodal cubic y 2 = x 3 + x 2 is a quantum homogeneous space, and Kraehmer and Martins refined this result in [16] to show that the containing Hopf algebra H can in this case be taken to be affine noetherian of Gel'fand-Kirillov dimension 1. From a slightly different perspective, some further embeddings of this sort appear in Liu's endeavour [21] aimed at extending the classification of prime affine Hopf k-algebras of Gel'fand-Kirillov dimension 1 to the non-regular case.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Goodearl and Zhang showed [11,Construction 1.2] that every cusp y m = x n , where m and n are coprime integers with m > n ≥ 2, is a quantum homogeneous space in a noetherian Hopf domain of Gel'fand-Kirillov dimension 2. In [17], Kraehmer and the second author showed that the nodal cubic y 2 = x 3 + x 2 is a quantum homogeneous space, and Kraehmer and Martins refined this result in [16] to show that the containing Hopf algebra H can in this case be taken to be affine noetherian of Gel'fand-Kirillov dimension 1. From a slightly different perspective, some further embeddings of this sort appear in Liu's endeavour [21] aimed at extending the classification of prime affine Hopf k-algebras of Gel'fand-Kirillov dimension 1 to the non-regular case.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…The study of quantum homogeneous spaces has been a pervasive theme of research in Hopf algebras over the past 25 years, from both the algebraic and analytic perspectives. For the algebraic point of view which concerns us here see, for example, [5,16,17,23,24,28].…”
Section: Amalgamatementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several such examples are known by now, which include: (i) (co)action of S + n on the connected compact space formed by topologically gluing n copies of a given compact connected space [18]; (ii) Co-action of the group C * algebra C * (S 3 ) of the group of permutations of 3 objects on the coordinate ring of the variety {xy = 0} as in [11] (iii) algebraic co-action of Hopf-algebras corresponding to genuine non-compact quantum groups on commutative domains associated with affine varieties as in [35](Example 2.20). (iv) Algebraic co-action of (non-commutative) Hopf algebras on the coordinate ring of singular curves like the cusp and the nodal cubic, given by Krahmer and his collaborators (see [23], [24]).…”
Section: Introductionmentioning
confidence: 99%